Inequality, Poverty and Development in India : Focus on the North Eastern Region - Bharati, Premananda; De, Utpal Kumar; Pal, Manoranjan (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book reviews the fulfillment of two Millennium Development Goals (MDGs), namely poverty and inequality, in the Indian subcontinent. It examines the complex interplay among development, inequality and poverty in relation to corruption, environmental resource management, agricultural adjustment to climate change and institutional arrangements, with a special focus on the Northeastern region of the country. The topics covered offer a blend of theoretical arguments and empirical data with regard to the three main themes of the book, while also providing agricultural and environmental perspectives. The book also provides guidelines for policy initiatives for harnessing the region's potential in the areas of industry, trade, sustainable use of mineral, forest and other natural resources, nature-based tourism through proper infrastructure development, and resolving land issues to achieve inclusive development. In addition to introducing some new questions on the development-ethnic conflict interface, it uses sophisticated tools such as the Blinder-Oaxaca decomposition method in consumption expenditure to show the endowment, and return to endowment effects; and techniques like spatial correlation-regression to analyze regional variation, co-integration, vector autoregression, the panel data technique and the adaptation index to climate change, to understand socio-economic complexities and the effect of the concerned variables on entrepreneurship and human development. The book offers a timely contribution to our understanding of major MDGs and highlights their successes and failures. It also includes analytical frameworks that are key to future policy initiatives. Further, it disseminates approaches and methods that improve livelihoods and standards of living through poverty reduction and promoting inclusive development along with sustainable utilization of available natural resources. Putting forward various ideas for creating a more sustainable future, it inspires and encourages readers to pursue further studies to address the gaps that still remain.
Part 1: Inequality, Growth and Development -- Chapter 1. Inequality, Growth and Development -- Chapter 2. Deficit Financing, Crowding out and Economic Growth: Bangladesh Perspective -- Chapter 3. Is Corruption Always Growth-Inhibitory? A Cross-National Study in Non-Linear Frame Work -- Chapter 4. Empirical Evaluation of Kuznets Hypothesis In Case of India -- Chapter 5. An Inquiry into the Dynamics of Inequality from the perspective of Caste -- Chapter 6. Can Horizontal Inequalities Explain Ethnic Conflicts? A Case Study of Bodoland Territorial Area Districts of Assam -- Chapter 7. Selection and Performance of Self Help Groups in West Bengal: A Case Study -- Chapter 8. Financial Inclusion through Kisan Credit Cards in Arunachal Pradesh - Is There District-Level Convergence? -- Chapter 9. Insurance and Banking Habits Regulating Economic Stability of the People of Char Areas (riverine) in Lower Assam -- Chapter 10. Institutional Barriers to Development in the State of Nagaland.- Part 2: Poverty -- Chapter 11. A Study of Multidimensional Poverty in North-East India -- Chapter 12. A Study of Multidimensional Poverty in North-East India -- Chapter 13. Poverty, Food Consumption Pattern and Nutritional Outcomes in North-East India -- Chapter 14. Levels of Living in the North Eastern States of India -- Chapter 15. Levels of Living in the North Eastern States of India -- Chapter 16. Rural Poverty and Employment Guarantee Scheme: Observation from West Bengal -- Chapter 17. Poverty in Rural West Bengal: Trend Over Four Decades -- Chapter 18. Poverty in Rural West Bengal: Trend Over Four Decades -- Chapter 19. A Study on Spatial Statistical Method of Poverty and Sustainable Development of North-Eastern States of India -- Chapter 20. Hunger, Governance, Failure and Its Outcome: An Analysis of the Historical Experience of the Mizo Hill Districts of Undivided Assam -- Chapter 21. Conflicts Leave a Trail of Poverty and Malnutrition: Evidences from Assam.- Part 3: Agricultural and Environmental Perspectives -- Chapter 22. Integrated Management of Aqua-Terrestrial Ecosystem for Enhancing Productivity, Economic Stability and Promoting Rural Livelihoods Sustainable for Indian Sub-Continent -- Chapter 23. Family Farming in Amazon: Solution to Food and Regional Competitiveness -- Chapter 24. Farm Growth in North-East India and Its Effect on Poverty -- Chapter 25. Socio-Economic and Environmental Performance across North-Eastern States of India -- Chapter 26. Adaptability of Farmers in Assam towards Extreme Climate Effects: An Empirical Investigation -- Chapter 27. Dynamics of Forest Resources: Some Empirical Testing on Assam's Forest Cover -- Chapter 28. Is Indian Agriculture Shifting towards Feminisation? : A Study on Recent Trend in Indian Agriculture with Reference to the Selected States of North-East India.
Description based on publisher-supplied MARC data.
Keywords: Development economics; Economic development; Poverty; Social change; Social inequality; Social structure; Development Economics; Development Aid; Development and Social Change; Social Structure, Social Inequality